Pengaruh Kualitas Nutrisi Kulit Buah Kakao (Theobroma cacao) melalui Fermentasi dengan Jamur Pelapuk Putih (Pleurotus ostreatus) - jati, putri zulia (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This research was conducted to determine the substrate composition, inoculum dose and fermentation time that are suitable for the growth of Pleurotus ostreatus on a substrate mixed with cocoa pod skin (KBK) with tofu dregs, soy milk dregs and bran on crude fiber content and crude fiber digestibility. This research used an experimental method with a 3x3x3 Factorial Completely Randomized Design (CRD) with 2 replications. Factor A is a substrate composition with a ratio of 80% cocoa pod skin and 20% each for tofu dregs, soy milk dregs and bran. Factor B is the inoculum dose, namely 6%, 8% and 10%, and factor C is the fermentation time, namely 7, 9 and 11 days. The results of the analysis showed that there was an interaction between substrate composition and fermentation time with Pleurotus ostreatus which had a significantly different effect (P0.05) on crude fiber content and crude fiber digestibility. The conclusion of this study was that the selected treatment was in the A1B3C2 treatment (80% cocoa pod skin and 20% tofu dregs at a dose of 10% with a fermentation time of 9 days) reducing crude fiber by 48.14% and crude fiber digestibility by 57.86%. .